2016
DOI: 10.1177/1363460715616949
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s better than daytime television’: questioning the socio-spatial impacts of massage parlours on residential communities

Abstract: 1 '"It's better than daytime television": questioning the socio-spatial impacts of massage parlours on residential communities' AbstractIt has been shown that street sex work is problematic for some communities, but there is less evidence of the effects of brothels. Emerging research also suggests that impact discourses outlined by residential communities and in regulatory policies should be critiqued, because they are often based on minority community voices, and limited tangible evidence is used to masquerad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Cis male profiles were the most likely to advertise out‐calls, and trans female profiles were the most likely to offer in‐calls (see Figure ). These findings challenge common assumptions held by the general public that there are designated spaces where sex is bought and sold (Cooper, ; Kingston, ). For example, out‐calling can offer opportunities for sex workers to separate “home” from “work” as part of broader strategies to manage the distinction between personal lives and sex working (Sanders, ).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Cis male profiles were the most likely to advertise out‐calls, and trans female profiles were the most likely to offer in‐calls (see Figure ). These findings challenge common assumptions held by the general public that there are designated spaces where sex is bought and sold (Cooper, ; Kingston, ). For example, out‐calling can offer opportunities for sex workers to separate “home” from “work” as part of broader strategies to manage the distinction between personal lives and sex working (Sanders, ).…”
Section: Resultssupporting
confidence: 52%
“…These findings are significant for the study of geographies of commercial sex, for it is often assumed that sex work is primarily concentrated in big cities, and that it is confined to particular spaces (such as brothels and red‐light districts) (Cooper, ). Our study suggests that the online sex industry may be rather more dispersed across the UK than is commonly thought.…”
Section: Resultsmentioning
confidence: 99%
“…The noise of sex workers and clients is also sometimes deemed to be anti‐social (Scoular et al ., ). It is noted in Cooper's () work that the legality of brothels is not always well understood by the public, which is not aided by inconsistent approaches to regulation by local authorities. This generates differential interpretations of them by individuals.…”
Section: Manifestations and Governance Of Sex Work In Blackpoolmentioning
confidence: 99%
“…A focus on brothels is important, given that street sex work has dominated academic literature, the media and public policy alike—despite indoor sex work being the more common form. That being said, scholars are beginning to investigate sex work in brothels (Sanders, ; Brents and Hausbeck, ; Cooper, ), residential homes (Hubbard and Prior, ), hotels (Kempadoo, ) and other spaces. Not only is there much for academics to explore about brothels and other forms of indoor sex work within cities, but there is even more that needs attention when it comes to the relationship between the visual/sensual, brothels and cities.…”
Section: Introductionmentioning
confidence: 99%
“…Stringent reforms around the permissibility of such establishments that clients can attend has been "stimulated by a perception of the inherent unlawfulness and disorderliness of brothels" (Crofts, 2007) rather than utilising an evidence-based approach which affirms these establishments operate in the same manner as other businesses. Emerging research has found that the amenity impact on neighbouring land uses and residents is minimal and can in fact be a positive factor for the community, through sex workers and clients contributing economically to local businesses and providing passive surveillance to increase real and perceived levels of safety (Cooper, 2016;Cooper & Maginn, 2016;Crofts & Prior, 2012b;Kingston, 2013;Prior & Crofts, 2012).…”
Section: Locations Where Clients Visitmentioning
confidence: 99%